(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
Health organizations are one of the sectors that the Kingdom of Saudi Arabia is keen to achieve its goals, as the provision of health care is one of the services that receive great attention from the state in improving the health status of the individual and the group; due to its importance in supporting the development process, and based on that, the interest in the role of workers in the health sector, which in turn made this sector occupy a distinguished position among other service sectors due to the importance imposed by the nature of the services provided by this sector due to its direct connection to the health and lives of members of society. From here, the current study was launched due to the necessity of addressing job satisfaction among workers in the health sector, by trying to investigate job satisfaction and work performance between employees of the general ladder and employees of the self-employment program, as there are differences in job titles and ladders and salaries, which may lead to a negative work environment through employee dissatisfaction and negatively affect the performance and motivation of employees to work. The study concluded with a set of recommendations, including the necessity of working to provide real development opportunities for employees to enhance job satisfaction for the institution’s employees, employee participation in building the goals and objectives of health institutions, and making decisions that affect them to contribute to raising their level of job satisfaction.